The motor-muscle requirements for different methods of opponenoplasty (experimental study) - Strafun, Sergiy; Oberemok, Mykola; Chkalov, Oleksiy; Yurchenko, Volodymyr; Timoshenko, Sergiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective: to determine in an experiment the ability of muscle-motors to provide the effectiveness of oponenoplasty techniques for which they are applied, including reducing of their power characteristics. Methods: simulation was carried out on 5 fresh cadavers hands and forearms. Comparative analysis of the 7 most prevalent methods of opponenoplasty was made. The techniques were differed by selecting of the muscle, block-suture and tendon insertion points to the different thumb structures. The tension for transposed tendons has carried out through an electronic dynamometer with recording of force, excursion, and amplitude of the thumb deviation. We calculated the necessary strength and the work of the transposed muscle to realize the effectiveness of the techniques in angular indices and in points by Kapandji. Results: physiological characteristics of the target muscle-motors (forces, amplitudes and work parameters) were enough for Steindler, Thompson, and Bunnell techniques effectiveness in all insertion variants. However, do not effective enough to the parameters of insufficient physiological excursion for Guber methods, and were not insufficient by force and work parameters for Edgerton-Brand, Burkhalter and Taylor methods. When the strength of the target muscleengine decreases to the M4 level, the effectiveness of the tested techniques significantly decreases: Thompson — up to 2 points by Kapandji, Steindler and Bunnell — up to 1–2, for others — tends to zero. Conclusions: in experimental study with physiological parameters and a functional state of the muscle-motor up to M5 — most of the opponenoplasty are effective, with a decrease in its strength to M4 — are ineffective. The obtained data allowed us to select the method of opponenoplasty according to the resources and functional state of the muscle-motor and to predict the effectiveness of treatment.